Notre-Dame des Amériques : la Vierge de Guadalupe (Mexique) - Sylvie Mégevand (Caravelle)
A symbol of popular faith, a syncretic figure, Our Lady of Guadalupe occupies a predominant place in Hispano American’s rich imagination. This study aims to determine, through a few significant phases of its history, the characteristics which turn out this Marian image into a religious and identity icon, acknowledged by believers as well as by atheists.